IMPLEMENTASI KEBIJAKAN PEREMAJAAN SAWIT RAKYAT PADA PETANI SWADAYA DI DESA SARI GALUH KECAMATAN TAPUNG KABUPATEN KAMPAR TAHUN 2019-2021 - Amanda Sely Utami; Geovani Meiwanda (Universitas Halu Oleo, 2022)
To diminish issues in regards to the usefulness of smallholder oil palm manors through smallholder palm oil restoration, it is accepted to be the critical connection in expanding the efficiency of smallholder oil palm ranches and expanding the government assistance of ranchers. This study has a reason, specifically to decide the outcome of the smallholder oil palm restoration program for free smallholders in the Sari Galuh town, Tapung area, Kampar region and the variables that become hindrances in the execution of smallholder oil palm revival arrangements. The hypothetical idea that the analyst utilizes is the hypothesis of strategy execution by Edward III 2019. By utilizing subjective examination strategies and information assortment procedures in view of meetings, perceptions and documentation. The consequences of the examination that the creators get are the execution of smallholder oil palm restoration on autonomous smallholders. In Sari Galuh Town, there are as yet a few factors that become obstructions experienced by the Kampar Rule Estate Administration, so the execution of smallholder oil palm restoration on free smallholders has not been compelling and has not been carried out appropriately and ideal.